Studies on Optimization of Papain Hydrolysis Conditions for Release of Glycosaminoglycans from the Chicken Keel Cartilage - Nguyen Thi Le Vien; Pham Bao Nguyen; Lam Duc Cuong; Trinh Thi Thua An; Dong Thi Anh Dao (New Visions in Science and Technology Vol. 1, 2021)
This study focused on the optimization of papain hydrolysis conditions (pH, E/S ratio, incubation temperature and hydrolysis time) for receiving of glycosaminoglycans from the chicken keel cartilages. Glycosaminoglycans (GAGs) are natural biocompounds that unite to form cartilage tissuses in sharks, pigs, cows, chickens, and other animals. They can be isolated from cartilage of sharks, pigs, cows, chickens, and other animals. Chondroitin sulfate (CS), a supplement of functional food used to prevent and promote the treatment of arthritis and eye problems, is included in GAGs. Therefore, the GAGs extraction from byproducts of the industry of cattle and poultry slaughter to identify the CS content by papain enzyme is necessary. In this study, the optimal hydrolysis conditions were obtained by response surface methodology (RSM). The independent variables were coded as: pH (x1), enzyme concentration (x2), incubation temperature (x3) and hydrolysis time (x4). The findings of the analysis of variance (ANOVA) revealed that the variables had a significant impact on the content of GAGs.The best hydrolysis conditions were determined to be pH 7.1, 0.62 percent enzyme per substance w/wpo, 65°C, and a hydrolysis period of 230 minutes, with GAG content reaching 14.3 percent of the dry matter of the raw material. Analyzes by HPLC revealed that 56.17% of the dry preparations of GAGs were CS compound, were equivalent to 8.11% of the dry matter of chicken keel cartilage. Molecular weight of the dry preparations GAGs was 259.6 kDa. The dry preparations included the contents of moisture 12.2%, protein 8.42%, lipid 0%, ash 10.03% and extracted GAGs 69.35%. In this work papain used to hydrolyse chicken keel cartilage. The hydrolysis conditions were optimized by RSM using Mode 5.0 software. . This article contribute to make a product is good for health, high quality and reduce costs.